Antibody-dependent and spontaneous lympholysis in urologic cancer patients. - Ratliff, T. L. (Nature Publishing Group, 1979)
To evaluate cytotoxic function mediated by killer lymphocytes and macrophages in urological cancer patients, we examined antibody-dependent and spontaneous lympholysis of chicken erythrocyte target cells, which is mediated by macrophages. Our results demonstrate a discordance between cytotoxic mechanisms in cancer patients, killer-cell function being impaired whilst macrophage-mediated cytotoxicity was increased.